2017
DOI: 10.1038/srep41663
|View full text |Cite
|
Sign up to set email alerts
|

Interplay with the Mre11-Rad50-Nbs1 complex and phosphorylation by GSK3β implicate human B-Myb in DNA-damage signaling

Abstract: B-Myb, a highly conserved member of the Myb transcription factor family, is expressed ubiquitously in proliferating cells and controls the cell cycle dependent transcription of G2/M-phase genes. Deregulation of B-Myb has been implicated in oncogenesis and loss of genomic stability. We have identified B-Myb as a novel interaction partner of the Mre11-Rad50-Nbs1 (MRN) complex, a key player in the repair of DNA double strand breaks. We show that B-Myb directly interacts with the Nbs1 subunit of the MRN complex an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 48 publications
1
23
0
Order By: Relevance
“…In agreement with our conclusions, studies using human cell lines have recently demonstrated that MYBL2 interacts with Nbs1, which is required for the activation of ATM in response to DSBs and also ATM-dependent heterochromatic DSB repair in G 0 -G 1 (9). While on face value, this may explain our observations Mybl2 þ/D HSCs, in stark contrast to the work of Henrich and colleagues, we were unable to detect a G 2 -M checkpoint defect in our Mybl2-haploinsufficient HSCs, suggesting that at least some ATM-dependent signaling is intact in these cells.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In agreement with our conclusions, studies using human cell lines have recently demonstrated that MYBL2 interacts with Nbs1, which is required for the activation of ATM in response to DSBs and also ATM-dependent heterochromatic DSB repair in G 0 -G 1 (9). While on face value, this may explain our observations Mybl2 þ/D HSCs, in stark contrast to the work of Henrich and colleagues, we were unable to detect a G 2 -M checkpoint defect in our Mybl2-haploinsufficient HSCs, suggesting that at least some ATM-dependent signaling is intact in these cells.…”
Section: Discussionsupporting
confidence: 93%
“…Genetic alterations are often present in MDS and a frequent chromosome abnormality is del20q, whose common deleted region only contains 5 genes expressed in HSCs, one of which is MYBL2 (2,3). The MYBL2 gene encodes a ubiquitously expressed protein belonging to the MYB family of transcription factors and has been shown to form part of different protein complexes such as the Myb-MuvB/DREAM complex (4-7), Myb-Clafi complex (8), and the MRN complex (9), through which it exerts its vital role in cell-cycle regulation and maintenance of genome stability (10)(11)(12)(13)(14). Analysis of publicly available global gene expression data from CD34 þ -MDS patient cells (15) have confirmed that downregulation of MYBL2 expression correlates with poor prognosis; even in patients with a normal karyotype (2,3).…”
Section: Introductionmentioning
confidence: 99%
“…Upon DNA damage, p130 switches from a hyper-to a hypo-phosphorylated form (Mannefeld et al 2009, Quaas et al 2012. In addition, B-MYB is inactivated in response to DNA damage (Mannefeld et al 2009, Klein et al 2015, Henrich et al 2017. In proliferating cells, p130 is hyper-phosphorylated and binds to CDK2, but DNA damage leads to induction p21, which binds to CDK2, which in turn dissociates from p130, leading to hypophosphorylation of p130 (Quaas et al 2012) (Figure 4).…”
Section: Repression Of Cell Cycle Genes In Response To Cell Stress Anmentioning
confidence: 99%
“…Other interesting genes, such as Rad50 (BGIBMGA005449), which is associated with DNA repair functions [44][45][46] and the histidine triad protein gene (BGIBMGA011899), which plays roles in transcription, signal transduction and many peripheral and central nervous system diseases [47] are also shown different mRNA transcript level and DNA methylated level upon BmNPV infection (Table 1).…”
Section: Discussionmentioning
confidence: 99%